TINJAUAN TENTANG KEPEMILIKAN TANAH SECARA ABSENTEE / GUNTAI DI DESA PANDAU JAYA KECAMATAN SIAK HULU BERDASARKAN PERATURAN PEMERINTAH NOMOR 41 TAHUN 1964 TENTANG PERUBAHAN DAN TAMBAHAN PERATURAN PEMERINTAH NOMOR 224 TAHUN 1961 TENTANG PELAKSANAAN PEMBAGIAN TANAH DAN PEMBERIANGANTI KERUGIAN - Maha, Fandi Wahyudi; Bachtiar, Maryati; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
As an implementation of Law Number 5 of 1960 concerning Basic Regulationson Agrarian Principles (UUPA), the government issued Law Number 56 of 1960concerning Determination of Agricultural Land Area with the Implementation of PPNumber 224 of 1961 concerning Implementation of Land Distribution and ProvidingCompensation, in Article 3 paragraph (1) of PP Number 224 of 1961 in conjunctionwith Article PP Number 41 of 1964 regulates the Prohibition of Absentee LandOwnership, in reality There are still people who own agricultural land in absentee inPandau Jaya Village, Siak Hulu District, so in practice the regulations regarding theprohibition of absentee land cannot be implemented effectively.This type of research is classified as sociological legal research. Insociological legal research, the data sources are primary data sources and secondarydata sources consisting of primary legal materials, secondary legal materials andtertiary legal materials. Collecting normative legal research data uses datacollection techniques by interview and literature study. Data obtained throughliterature study will be analyzed qualitatively. In drawing conclusions the author usesan inductive thinking method, namely a way of thinking that draws conclusions froma specific statement or proposition to a general statement.Based on the research results, it can be understood that the factors that occurin absentee land ownership by inheritance in Pandau Jaya Village, Siak HuluDistrict, Kampar Regency include: buying and selling factors, inheritance factors,village coordination factors, absentee land data completeness factors and legalconsequences of absentee land ownership by inheritance in the Village Pandau Jaya,Siak Hulu District, Kampar Regency. In accordance with the principles of landreform contained in article 10 of the Basic Agrarian Law Number 5 of 1960 whichprohibits owning land in absentee. So, indirectly, absentee ownership of land resultsin the agricultural land not being able to be registered with BPN Kampar Regency asa Certificate of Ownership.Keywords: Ownership – Absentee Land – Pandau Jaya Village